Potential of Plant-Based Extracts to Alleviate Sorbitol-Induced Osmotic Stress in Cabbage Seedlings - Katarzyna Pacyga; Paweł Pacyga; Aleksandra Boba; Bartosz Kozak; Łukasz Wolko; Yelyzaveta Kochneva; Izabela Michalak (Plants, 2024)
In light of expected climate change, it is important to seek nature-based solutions that can contribute to the protection of our planet as well as to help overcome the emerging adverse changes. In an agricultural context, increasing plant resistance to abiotic stress seems to be crucial. Therefore, the scope of the presented research was focused on the application of botanical extracts that exerted positive effects on model plants growing under controlled laboratory conditions, as well as plants subjected to sorbitol-induced osmotic stress. Foliar spraying increased the length and fresh mass of the shoots (e.g., extracts from Taraxacum officinale, Trifolium pratense, and Pisum sativum) and the roots (e.g., Solidago gigantea, Hypericum perforatum, and Pisum sativum) of cabbage seedlings grown under stressful conditions, as well as their content of photosynthetic pigments (Pisum sativum, Lens culinaris, and Hypericum perforatum) along with total phenolic compounds (Hypericum perforatum, Taraxacum officinale, and Urtica dioica). The antioxidant activity of the shoots measured with the use of DDPH (Pisum sativum, Taraxacum officinale, Urtica dioica, and Hypericum perforatum), ABTS (Trifolium pratense, Symphytum officinale, Valeriana officinalis, Pisum sativum, and Lens culinaris), and FRAP (Symphytum officinale, Valeriana officinalis, Urtica dioica, Hypericum perforatum, and Taraxacum officinale) assays was also enhanced in plants exposed to osmotic stress. Based on these findings, the most promising formulation based on Symphytum officinale was selected and subjected to transcriptomic analysis. The modification of the expression of the following genes was noted: Bol029651 (glutathione S-transferase), Bol027348 (chlorophyll A-B binding protein), Bol015841 (S-adenosylmethionine-dependent methyltransferases), Bol009860 (chlorophyll A-B binding protein), Bol022819 (GDSL lipase/esterase), Bol036512 (heat shock protein 70 family), Bol005916 (DnaJ Chaperone), Bol028754 (pre-mRNA splicing Prp18-interacting factor), Bol009568 (heat shock protein Hsp90 family), Bol039362 (gibberellin regulated protein), Bol007693 (B-box-type zinc finger), Bol034610 (RmlC-like cupin domain superfamily), Bol019811 (myb_SHAQKYF: myb-like DNA-binding domain, SHAQKYF class), Bol028965 (DA1-like Protein). Gene Ontology functional analysis indicated that the application of the extract led to a decrease in the expression of many genes related to the response to stress and photosynthetic systems, which may confirm a reduction in the level of oxidative stress in plants treated with biostimulants. The conducted studies showed that the use of innovative plant-based products exerted positive effects on crops and can be used to supplement current cultivation practices.